Distributing the personal digital environment throughout your entertainment environment: Handling personal metadata across domains - Lugmayr, Artur; Reymann, S.; Bruns, V.; Rachwalski, J.; Kemper, S. (Springer, 2009)
It is a fact, that we are surrounded by more and more ubiquitous services in entertainment computation. All sorts of devices are more and more connected, and personalization becomes more and more a major issue. We are living in a world with two layers: the real physical layer being our real-world, and its synthetic overlay consisting of location-based services, chatting applications, or Web 2.0 offers. In the real-world, communication between humans is a matter of personality of different persons: exchanging information about each other, finding common interests, or finding common conversation themes. In the synthetic overlay, communication becomes a matter of distribution of personal profiles or automating profile matching. The open-source platform Portable Personality (P2) ( www.portable-personality.org ) faces this challenge, and provides a platform for cross-service interchange of personal context information based on any generic metadata type. P2's software architecture is designed for mining, enriching, and exchanging personal profiles between arbitrary multimedia services. The long-term vision of P2 is to provide a personality profile rather than a personal context information profile to enable communication between human and device as a matter of personalities, rather than automated matching of profiles. Two different scenarios, the Smart Social Network (SSN), and the personalization of audio-visual data are presented as practical use-case for P2. © 2009 Springer-Verlag.